From Anna - Little, Jean, 1932-; Sandin, Joan (New York : Harper & Row, 1972)
When the family moves from Germany to Canada in the 1930's, a nine-year-old girl discovers the reason for her awkwardness and apparent inability to do anything right.
Keywords: People with disabilities -- Fiction